(untitled) (Al-Mansour Journal, 2023)
The exert of reform and management development as it self as objective exert develop the capacities of institutional building the strategy of modern states ( as well as the essential; planning and activities foe economic, social and cultural development ) . Therefore the feasibility and exert of the reform and management development for u[grading the capabilities and human skills enrichment of the institution system is depend on the creation of a development methodology a reverse to the transfer simulation which can create also an new ( O&M ) organization and methods mutual with environment requirement as well as the modern development ( place& time) requirements . So, it is necessary to increase and expand the abilities of creative and intellectual thinking skills for manpower within deferent managerial organization in order to cope with the new challenging that having faced now a days . The intellectual thinking is considered the creation of computability between methodology and facts by using new techniques depending or personal capacities in thinking and planning . For such trends in managerial reform end development raising a set of questions the rel researcher try to discuses to find the logical relationships between managerial reform ( such as , values, principle) which can be used as a basis for the institution to reach to the priority and integrity ? what is the requirements of the creative institution organization climate .